PENGARUH SET KEPUTUSAN INVESTASI, TATA KELOLA PERUSAHAAN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2018-2021 - I Gusti Ngurah Putra Harthawan; Melita Isti Septiasari; Ni Ketut Ragil Oktaviani (Faculty of Economics and Business, Universitas Warmadewa, 2023)
The purpose of this study was to determine the significance of the effect of investment opportunity sets on firm value in the banking sector on the Indonesia Stock Exchange, to determine the significance of the effect of corporate governance on firm value in the banking sector on the Indonesia Stock Exchange, to determine the significance of the effect of profitability on firm value in the banking sector on the Stock Exchange. Indonesian Securities. The methods used in this study are the methods used in collecting the data needed in this study are as follows: a study of literature from literary sources as a basis for analyzing the problems compiled in this study. Observation is carried out by direct observation of the object to be studied related to the problem to be discussed. The data collection technique in this study is a company that enters the banking sector and is listed on the Indonesia Stock Exchange 2018-2021. While the selection of samples using purposive sampling method. Samples were selected with the following criteria: Banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2018 to 2021 Publish complete financial statements (income statement, balance sheet) with the period ending December 31, continuously from 2018-2021. The company's shares remain actively operating until August 31, 2021. The analytical method used is descriptive statistical analysis, classical assumption test and hypothesis testing. The hypothesis is tested by multiple linear analysis. Ghozali (2013) said that multiple regression analysis is the relationship of two or more variables and shows the direction of the relationship between the dependent variable and the independent variable. The following is the linear regression equation that is formed: Y = α + β1X1 + β2X2 + β3X2 + ε Before testing the hypothesis, it is necessary to test the classical assumptions. In this study the data used was pool data, namely a combination of cross sectional and time series so that the autocorrelation test was not needed in testing this study. Autocorrelation test is the data used in time series data. This test aims to see whether in a linear regression there is a correlation between confounding errors in period t and errors in period t-1 or earlier. Autocorrelation test can be done with the Durbin-Watson (DW) test, (Ghozali, 2013). The classic assumption test that will be used is the normality test, multicollinearity, and heteroscedasticity.